Determination of a novel pesticide cyetpyrafen and its two main metabolites in crops, soils and water. (30th January 2023) - Wang, Sijia; Li, Runan; Dong, Fengshou; Zheng, Yongquan; Li, Yuanbo
Graphical abstract: Highlights: We firstly developed an analytical method for cyetpyrafen and its metabolites. The uptake and metabolism of cyetpyrafen in soil–strawberry system was evaluated. Cyetpyrafen and M−309 mainly accumulated in strawberry fruits by foliar spray. Cyetpyrafen showed poor top-down and bottom-up movement within plants. The dissipation of cyetpyrafen in orange fruits and peels was examined. Abstract: Novel insecticide cyetpyrafen is frequently used in various crops, however, knowledge of its fate in crops and environments is largely unexplored. In this study, an effective method was firstly established for simultaneous determination of cyetpyrafen and its metabolites (M−309 and M−391) in 13 matrices (e.g., plants and soils) to explore their fate. Mean recoveries of the three compounds ranged from 73.1 % to 118.7 % with the relative standard deviations (RSDs) less than 17.9 %. Further, after 28 days of exposure in a field soil-strawberry system, cyetpyrafen and M−309 exhibited great accumulations in strawberry leaves by foliar spray while both compounds were predominately accumulated in roots by root irrigation, where cyetpyrafen was poorly translocated within plant. An equal amount of M−309 was measured in both strawberry plants and soils indicates the extensive transformation of cyetpyrafen in soil-strawberry system. Therefore, metabolism of cyetpyrafen in foods need to be considered for its better risk assessment.